The Lived Contestations of Adivasi Catholic Identity-Making - D’Souza, Rinald (Ecclesial practices, 2022)
In the mid-nineteenth century movement towards Christianity in Chotanagpur in central India, the missionary Constant Lievens (1856–1893) played a pioneering role in the establishment of the Catholic Mission among the Adivasis (indigenous peoples). Through Lievens’ legal advocacy, Adivasis not only adopted a faith, but also began to reclaim their lands and their indigeneity. Drawing on ethnographic research around the intercessory prayer for the beatification of Lievens, this paper analyses the present-day lived contestations of Adivasi Catholic identity-making. The paper argues that Adivasi Catholic identities are lived in contestation and continuous negotiation with their present realities, while also borrowing from the legacies of their own past struggles and their intermediaries.